QUID PRO QUO: HOW POLITICAL CLIENTELISM MODERATES THE EFFECT OF ECONOMIC SHOCKS ON APPROVAL RATINGS - Kurmashev, Magzhan (School of Sciences and Humanities, 2023)
This Master's Thesis researches the moderating effect of political clientelism on negative economic conditions that affect the approval ratings of incumbent politicians, namely the president or the prime minister. The study examines the extent to which clientelistic linkages between voters (clients) and political figures or parties (patrons) can moderate the relationship between economic indicators and the approval ratings of the incumbents. Using a quantitative methods approach, the research analyses Time-Series Cross-Section data that includes approval ratings of incumbent presidents or governments; key economic indicators, such as inflation, unemployment, national currency depreciation, and the GDP growth rate; the political clientelism index; and control variables of the honeymoon effect (first year in office). The data sample is made up of observations in 14 countries that arrive from different regions of the globe: North America, Latin America, Western Europe, the Middle East, and East Asia. The results are mixed. On the one hand, we see that political clientelism has a significant positive marginal effect on approval ratings. On the other hand, the results indicate that the moderating effect of political clientelism has no significant impact on the link between economic indicators and incumbent approval ratings. The study contributes to the existing literature on political clientelism by emphasising its significance for comprehending the dynamics of political approval ratings in nations with different tiers of democracy and freedoms, as well as economic development. Further studies are needed in this direction in order to develop new perspectives about the relationship between the literature on approval ratings and the literature on political clientelism.
Keywords: Type of access: Restricted; political clientelism; QUID PRO QUO; economic conditions